3D numerical modelling of negative apparent conductivity anomalies in loop-loop electromagnetic measurements: a case study at a dacite intrusion in Sugisawa, Akita Prefecture, Japan. Issue 3 (1st September 2017) - Selepeng, Ame Thato; Sakanaka, Shin'ya; Nishitani, Tadashi
Abstract : Under certain geological conditions, low induction number electromagnetic (LIN-EM) instruments are known to produce negative apparent conductivity ( σ a ) responses. This is particularly the case when the shallow subsurface is characterised by highly conductive bodies, however little attention has been given to this issue in the research literature. To analyse negative σ a anomalies and their causative structures, we make use of a 3D integral equation forward modelling technique based on a 3D weighting function. We present 3D numerical modelling results over a volcanic tuff body intruded by several dacite dikes, in Sugisawa, Akita Prefecture, Japan. Apparent conductivity data were acquired using a Geonics EM-34–3 system in the horizontal magnetic dipole (HMD) and vertical magnetic dipole (VMD) operating modes. Our 3D model resolved the horizontal and vertical extent of the dacite dikes and also delineated a high conductive zone between the volcanic tuff and the intrusive dacite dikes. This zone is the causative structure for negative σ a responses in the VMD data, and is interpreted to be an alteration zone. Interestingly, the negative σ a response was absent when the instrument alignment azimuth was changed, implying an anisotropic effect on the EM signature in the study area. The true conductivity model achieved by 3D forward modelling is shown to compare favourably with the DC resistivity data acquired in the same area. Abstract : Under certain geological conditions, low induction number electromagnetic instruments are known to produce negative apparent conductivity responses. This is particularly the case when the subsurface is characterised by highly conductive bodies. We present 3D numerical modelling results of dacite dike intrusions in Sugisawa, Akita Prefecture, Japan.